Advances in production of bioplastics by microalgae using food waste hydrolysate and wastewater: A review. (December 2021) - Chong, Jun Wei Roy; Khoo, Kuan Shiong; Yew, Guo Yong; Leong, Wai Hong; Lim, Jun Wei; Lam, Man Kee; Ho, Yeek-Chia; Ng, Hui Suan; Munawaroh, Heli Siti Halimatul; Show, Pau Loke
Graphical abstract: Highlights: Utilizing food waste hydrolysate and wastewater for bioplastic production. Heterotrophic microalgae growth utilizing food waste hydrolysates. Food processing wastewater for bioremediation and cultivation from microalgae. Food waste extraction techniques to be incorporated into bioplastic production. Abstract: Microalgae have emerged as an effective dual strategy for bio-valorisation of food processing wastewater and food waste hydrolysate which favours microalgae cultivation into producing value-added by products mainly lipids, carbohydrates, and proteins to the advantages of bioplastic production. Moreover, various microalgae have successfully removed high amount of organic pollutants from food processing wastewater prior discharging into the environment. Innovation of microalgae cultivating in food processing wastewater greatly reduced the cost of wastewater treatment compared to conventional approach in terms of lower carbon emissions, energy consumption, and chemical usage while producing microalgae biomass which can benefit low-cost fertilizer and bioplastic applications. The study on several microalgae species has all successfully grown on food waste hydrolysates showing high exponential growth rate and biomass production rich in proteins, lipids, carbohydrates, and fatty acids. Multiple techniques have been implemented for the extraction of food wastes to be incorporate into the bioplastic production.